ȻENTOL TŦE TEṈEW̱ (together with the land): Part 1: Indigenous land- and water-based pedagogies - Mowatt, Morgan; de Finney, Sandrina; Wright Cardinal, Sarah; Mowatt, Gina; Tenning, Jilleun; Haiyupis, Pawa; Gilpin, Erynne; Harris, Dorothea; MacLeod, Ana; Claxton, Nick (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
This article presents reflections from an Indigenous land- and water-based institute held from 2019 to 2020 for Indigenous graduate students. The institute was coordinated by faculty in the School of Child and Youth Care at the University of Victoria and facilitated by knowledge keepers in local W̱SÁNEĆ and T’Sou-ke nation territories. The year-long institute provided land-based learning, sharing circles, online communication, and editorial mentoring in response to a lack of Indigenous pedagogies and the underrepresentation of Indigenous graduate students in frontline postsecondary programs. While Indigenous faculty and students continue to face significant, institutionally entrenched barriers to postsecondary education, we also face growing demands for Indigenous-focused learning, research, and practice. In this article, Part 1 of a two-paper series on Indigenous land- and water-based learning and practice, we draw on a storytelling approach to share our individual and collective reflections on the benefits and limitations of Indigenous land- and water-based pedagogies. Our stories and analysis amplify our integration of Indigenous ways of being and learning, with a focus on local knowledges and more ethical land and community engagements as integral to Indigenous postsecondary education.